Antioxidant changes during domestic food processing of the white shaft and green leaves of leek (Allium ampeloprasum var. porrum). (16th October 2013) - Bernaert, Nathalie; De Loose, Marc; Van Bockstaele, Erik; Van Droogenbroeck, Bart
Abstract BACKGROUND Evaluating the effect of domestic cooking on the health benefits of vegetables has great practical importance. However, only a limited number of reports provide information on the effect of these treatments on the antioxidant capacity, polyphenol and S‐alk(en)yl‐l‐cysteine sulfoxide (ACSO, e.g. isoalliin and methiin) content of the white shaft and green leaves of leek (Allium ampeloprasum var. porrum). RESULTS In the present study, the antioxidant capacity of leek was highly influenced by cooking (blanching, boiling and steaming). Boiling had a negative effect on total phenolic content in the white shaft and green leaves. An obvious increase could be observed in the antioxidant capacity of the steamed green leaves, while steaming did not influence the polyphenolic content. Remarkably, blanching resulted in a slight increase in the ACSO content. Subjecting leek samples to a longer thermal treatment appeared to have a negative influence on the ACSO content in leek. Steaming was also responsible for a decrease in ACSOs. Methiin was less susceptible to heat treatment than isoalliin. CONCLUSION In general, steaming appeared to be responsible for better retention of the bioactive compounds present in leek compared with boiling. © 2013 Society of Chemical Industry